Desenvolvimento in vitro de embriões bovinos usando células-tronco mesenquimais de rato e fibroblastos embrionárias de camundongos - MARTINS, Sávio S. C. (2015)
Due to the importance of in vitro embryo production (IVEP) to accelerate genetic improvement is important the search for technological innovation that can enhance the in vitro embryo development. Mouse embryonic fibroblasts (MEFs) have been widely used as a feeder layer to support embryonic stem cells due to their release of growth factors. Mesenchymal stem cells (MSCs) from different sources were also found to release bioactive factors that can support cell growth. This study aims to investigate the effect of co-culture of MSC from rat bone marrow or MEF as a feeder source for in vitro production of bovine embryos. Cumulus oophorus complexes were matured into three groups: control (CTRL), co-culture with monolayer of mesenchymal cells of rats (MSC) or co-cultured with monolayer of embryonic fibroblasts of mice (MEF). Fertilization was performed in control condition for all groups, and in vitro fertilized embryos were cultured from fourth day on in CTRL, co-culture with MSC or co-cultured with MEF, so that the following groups were performed: (CTRL / CTRL) - maturation and embryo development in CTRL conditions; (CTRL / MSC) - maturation in CTRL and embryo development with MSC from the fourth day on after the beginning of the in vitro embryo culture; (CTRL / MEF) - maturation CTRL and embryo development with MEF from the fourth day on after the beginning of the in vitro embryo culture; (MSC / CTRL) - MSC during maturation and embryo development in CTRL; (MSC / MSC) - maturation and embryo development in MSC from the fourth day on after the beginning of the in vitro embryo culture; (MEF / CTRL) - maturation and embryo development in MEF and CTRL (MEF / MEF) - maturation and embryo development in MEF from the fourth day on after the beginning of embryo development in vitro. No significant difference was found among the oocytes matured in CTRL, MSC and MEF conditions for metaphase II and apoptosis rates and for cleavage rate in embryos at 4th day after the beginning of the in vitro culture. The number of cells in the inner cell mass, trophoblast cells, apoptotic cells and total cells were similar (P> 0.05) in the embryos from all experimental groups. The rates of blastocyst formation, expanded, hatched and the total of blastocysts did not differ among experimental groups (P> 0.05) at 7th day of embryo development. At eighth day of embryo culture we observed a difference (P <0.05) in hatched blastocyst rate which was higher in the CTRL /CTRL group when compared to MSC/MSC group, however, the proportion of blastocyst, expanded and total blastocysts was not different (P> 0.05). We conclude that there was no significant improvement in bovine embryo development using co-cultures of MSC from rats or MEF when compared to control culture system. However more studies investigating the use of stem cells from other sources or their conditioned medium are needed to better understand the effect of these cells on embryonic development.